PENGEMBANGAN KURIKULUM PAI - Susilawati Susilawati (ADISAM PUBLISHER, 2024)
The development of the Islamic Religious Education (PAI) curriculum continues to develop in line with the changes occurring in the current education system. This article discusses the development of the PAI curriculum, including the challenges faced and the strategies implemented in the development process. The main challenges faced include changes and rapid developments in education, globalization and increasingly advanced technology as well as changes in student needs. To overcome this challenge, several PAI curriculum development strategies have been implemented, including: integrating technology and digital learning media, implementing a competency-based approach, increasing active participation from all parties involved in curriculum development, and improving the quality of PAI teachers through training and professional development. . By identifying challenges and implementing appropriate strategies, PAI curriculum development can be more effective and successful in supporting students' successful learning in the field of Islam.